New sporopollenin-based β-cyclodextrin functionalized magnetic hybrid adsorbent for magnetic solid-phase extraction of nonsteroidal anti-inflammatory drugs from water samples - Yaacob, Syed Fariq Fathullah Syed; Kamboh, Muhammad Afzal; Wan Ibrahim, Wan Aini; Mohamad, Sharifah (The Royal Society, 2018)
A magnetic solid-phase extraction (MSPE)procedure on the newly synthesized magnetic β-cyclodextrin functionalized with toluene diisocyanate (TDI)as a linker and further modified with bio-polymeric spores of sporopollenin (MSp-TDI-βCD), was developed for the extraction of nonsteroidal anti-inflammatory drugs (NSAIDs), namely, indoprofen (INP), ketoprofen (KTP), ibuprofen (IBP)and fenoprofen (FNP)from water samples prior to their HPLC-DAD determination. The newly synthesized MSp-TDI-βCD was comprehensibly characterized using FT-IR, XRD, SEM-EDX, BET and VSM analyses. The separation of selected NSAIDs on MSp-TDI-βCD from aqueous solution was simply achieved by applying an external magnetic field via a permanent magnet. The MSPE parameters affecting extraction performance, i.e. sorbent dosage, sample volume, extraction and desorption time, type of organic eluent and volume and solution pH were investigated and optimized. The proposed method showed linear range between 0.5 and 500 ng ml-1, low limit of detection at S/N=3 (0.16-0.37 ng ml-1)and limit of quantification at S/N=10 (0.53-1.22 ng ml-1). The inter-day (n=15)and intra-day (n=5)precision for the proposed methods given by relative standard deviation (RSD%)was in the range of 2.5-4.0 and 2.1-5.5, respectively. The extraction recoveries of NSAIDs from environmental samples (tap, drinking and river water)ranged from 92.5% to 123.6%, with satisfactory precision (RSD% less than 12.4%).